Music Pedagogy in the 21st Century - Bräm, Thüring (Musica Docta, 2012)
<!--StartFragment--> The article begins with considering what are the qualities you need in education to lead you to success? One important factor for moving from failure to success is (as also pointed out by a recent New York Time article on educational programs in general ) is the factor of 'grit’. The question of 'What is teaching about?’ is explored on the basis of three case histories: that of a middle aged music teacher, of a young performing pianist and of a cello master student. Finally, a brief historical overview of the last 50 years looks at the larger changes which have taken place in the teaching of young instrumental students. It discusses methods being used ranging from training virtuoso skills (Czerny/Cramer) to applying insights about the cognitive development (Piaget) and neuroscience to the increasingly wide range of research topics on music pedagogy today.